-3(6p+5)-2(4-17p)=3(8+5p)

Simple and best practice solution for -3(6p+5)-2(4-17p)=3(8+5p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6p+5)-2(4-17p)=3(8+5p) equation:


Simplifying
-3(6p + 5) + -2(4 + -17p) = 3(8 + 5p)

Reorder the terms:
-3(5 + 6p) + -2(4 + -17p) = 3(8 + 5p)
(5 * -3 + 6p * -3) + -2(4 + -17p) = 3(8 + 5p)
(-15 + -18p) + -2(4 + -17p) = 3(8 + 5p)
-15 + -18p + (4 * -2 + -17p * -2) = 3(8 + 5p)
-15 + -18p + (-8 + 34p) = 3(8 + 5p)

Reorder the terms:
-15 + -8 + -18p + 34p = 3(8 + 5p)

Combine like terms: -15 + -8 = -23
-23 + -18p + 34p = 3(8 + 5p)

Combine like terms: -18p + 34p = 16p
-23 + 16p = 3(8 + 5p)
-23 + 16p = (8 * 3 + 5p * 3)
-23 + 16p = (24 + 15p)

Solving
-23 + 16p = 24 + 15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-15p' to each side of the equation.
-23 + 16p + -15p = 24 + 15p + -15p

Combine like terms: 16p + -15p = 1p
-23 + 1p = 24 + 15p + -15p

Combine like terms: 15p + -15p = 0
-23 + 1p = 24 + 0
-23 + 1p = 24

Add '23' to each side of the equation.
-23 + 23 + 1p = 24 + 23

Combine like terms: -23 + 23 = 0
0 + 1p = 24 + 23
1p = 24 + 23

Combine like terms: 24 + 23 = 47
1p = 47

Divide each side by '1'.
p = 47

Simplifying
p = 47

See similar equations:

| 7(3x-4)-7=70 | | .24x-.2=.14x+1-.5x | | 5x-24=-32+9x | | 2x-1y=-34 | | 24x^2+62x+14= | | -9(-4v+4)+-3v+-6= | | (y-2)(y-1)=2(y-2)(y-3) | | 6x^4-20x^3+16x^2= | | 3x-5b=10x | | Y^2-18Y+45=O | | log(7x+6)=2 | | 2a-3=16 | | 42q^2+17qd-15d^2= | | x(x^2-5x-6)=0 | | 10+9(8+5c)= | | f(x)=3x^2-2x+6 | | x+28=25 | | 56v^2+17vb-3b^2= | | 8+2x-4=6+4(x-1) | | 8+2x-4=6+4 | | -5(-9+-10t)+10(3+-5t)= | | 3[x+2(x-7)]=-60 | | 5x+28=35 | | 6-(-5)r=5r-3 | | -9(-1+-4k)+k= | | 2(x+4)=6-1(3x-2)-1 | | Y=log[4](x^2-4x-21) | | x-7=-.25 | | 8x-29=-77+2x | | 7x-28=17+2x | | 2(6x+6)+8=8x+18 | | 3(2a-2)=2(3a-3) |

Equations solver categories